Synthesis of 2-Azabicyclo[n.2.0]alkane-Derived Building Blocks - Grygorenko, Oleksandr O.; Kurkunov, Maksym; Levandovskiy, Igor A.; Tymtsunik, Andriy V. (Synthesis, 2018)
An approach to 2-azabicyclo[n.2.0]alkane derivatives (n = 1, 2), which relies on a tandem Strecker reaction–intramolecular nucleophilic cyclization (STRINC) sequence of the corresponding 2-(ω-chloroalkyl)cyclobutanones (in turn prepared by [2+2] cycloaddition of keteniminium salts and ethylene) is described. The utility of the method is demonstrated by multigram syntheses of bicyclic proline analogues, monoprotected diamines, as well as parent 2-azabicyclo[4.2.0]octane.
Keywords: cycloaddition; bicyclic compounds; amino acids; conformational restriction; cyclobutanes; nitrogen heterocycles; keteniminium salts; Strecker reaction